The complete mitochondrial genome of blacktip sardinella, Sardinella melanura (Clupeiformes: Clupeidae) - Sapto Andriyono; Md. Jobidul Alam; Sinar Pagi Sektiana; Hyun-Woo Kim (Mitochondrial DNA. Part B. Resources, 2019)
The mitochondrial genome of a blacktip sardinella, Sardinella melanura was determined by high-throughput sequencing (HTS) technique. The mitogenome of S. melanura (16,646 bp), encoded the canonical 37 mitochondrial structural genes (13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes). The gene arrangement of S. melanura was identical to its relative species including Sardinella lemuru, Sardinella longiceps and Sardinella gibbosa. Except for COX1 (GTG), all the other PCGs showed the typical ATG as start codon. Incomplete stop codons were identified in ND2, COX2, COX3, ND3, ND4, and Cytb. The phylogenetic tree result showed that S. melanura was most closely related to S. jussieu, S. lemuru, and Sardinella maderansis with 83% identity, respectively.